Paulistinha, a creche universitária da unifesp: a construção identitária de uma história multifacetada (1971 a 1996) - Oliveira, Rosana Carla De [UNIFESP] (2019)
This research aims to present a history of the Paulistinha University Nursery, of the Federal University of São Paulo - UNIFESP, an institution created in the 1970s to attend to children of the employees of Paulista Nursing School – EPE, attached to Paulista School of Medicine - EPM. Motivated by labor laws, two female employees claimed from the EPM board the right to take their children to the workplace, since they had no one to leave them with. After many discussions and conflicts, the request was answered and gave birth to the Children's Community, which later came to be called Paulistinha. The period to be examined will be from 1971, the year in which it was created, until 1996 when the nursery began to attend elementary school and acquired a new structural configuration. As a research methodology, the following procedures were used: literature review, document selection and analysis, collection, collection and selection of sources, and semi-structured interviews. Documents used by the Nursery and the Paulista Nursing School were used as sources, such as manuals, opinions, edicts, and personal documents of the interviewees, such as records, photographs and interviews. The interviews were carried out with the school's founders, employees and former employees, parents and alumni, in order to obtain information that could reconstruct the history of this institution. According to Magalhães (1998, 2004, 2011), school actions are part of a complex relationship that integrates dialectically, passing through the materiality, appropriation and representation in the production of a society. As second category was used the Representation of Place, according to Certeau (1976, 2014), the daily practices, the knowledge and the places of speech, as inseparable from a social institution, so that the stories transform the places into spaces of movement, considering the set of relationships associated with a story. As a third category, Memory was used under the perspective of Halbwachs (2006) Bosi (1994), who present the memories as constructions from a lived social context and that express identity, contradictory and moral issues from social frameworks that are revealed throughout the narratives. As results are indicated the permanences, ruptures and values acquired with the Schooling of the day care.